2022
DOI: 10.3390/nano12132134
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fingerprinting of the Omicron Variant Genome of SARS-CoV-2 by SERS Spectroscopy

Abstract: The continuing accumulation of mutations in the RNA genome of the SARS-CoV-2 virus generates an endless succession of highly contagious variants that cause concern around the world due to their antibody resistance and the failure of current diagnostic techniques to detect them in a timely manner. Raman spectroscopy represents a promising alternative to variants detection and recognition techniques, thanks to its ability to provide a characteristic spectral fingerprint of the biological samples examined under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…As previously shown for other SARS-CoV-2 variants, , the RNA Raman fractions do not generally match those obtained by genome analyses because of the combined effects of base-pairing, signal cross sections, and differences in viral nucleoproteins associated with preferential RNA sites . Such amplified differences in RNA-bases-related Raman signals is indeed a very fortunate circumstance since they enable viral speciation down to the subvariant level without the need of RNA sequencing and within a very short time of a Raman measurement (i.e., in the order of minutes). ,, …”
Section: Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As previously shown for other SARS-CoV-2 variants, , the RNA Raman fractions do not generally match those obtained by genome analyses because of the combined effects of base-pairing, signal cross sections, and differences in viral nucleoproteins associated with preferential RNA sites . Such amplified differences in RNA-bases-related Raman signals is indeed a very fortunate circumstance since they enable viral speciation down to the subvariant level without the need of RNA sequencing and within a very short time of a Raman measurement (i.e., in the order of minutes). ,, …”
Section: Results and Discussionmentioning
confidence: 89%
“…127 Such amplified differences in RNA-bases-related Raman signals is indeed a very fortunate circumstance since they enable viral speciation down to the subvariant level without the need of RNA sequencing and within a very short time of a Raman measurement (i.e., in the order of minutes). 33,34,128 The interaction between RNA viruses and host innate and adaptive responses represents a quite complex issue whose underlying mechanisms are generally multifactorial and conspicuously hidden in the details of enzymatic chemistry. Based on bioinformatics studies, 129,130 it has been suggested that RNA viruses are capable of adapting their genome to inhibit and divert the innate cell defenses beyond the process of merely coding it for developing structural and nonstructural proteins for virion assembly and genome replication.…”
mentioning
confidence: 99%
“…The data processing such as background subtraction and smoothening was performed using the second derivative and adjacent averaging method, respectively, present in the Origin 2020b software . The amide I region was deconvoluted by fitting Voigt profiles corresponding to the expected amide I vibrations of individual secondary structures, as reported elsewhere. , …”
Section: Methodsmentioning
confidence: 99%
“…39 The amide I region was deconvoluted by fitting Voigt profiles corresponding to the expected amide I vibrations of individual secondary structures, as reported elsewhere. 40,41 Computational Methods. The crystallographic structure of Lyz was taken from the RCSB protein data bank (PDB ID 1AKI).…”
Section: = [ ]mentioning
confidence: 99%
“…Although sensitive, the process of conjugating gold nanoparticles and antibodies takes more than three hours, and the total analysis requires at least 40 minutes. Leonardi et al (2022), 27 explored surface-enhanced Raman scattering (SERS) to reveal, for the first time, the vibrational fingerprints of the genome of the SARS-CoV-2 Omicron variant. Silver dendrites allowed quick and univocal discrimination of this variant through vibrational evaluations.…”
Section: Introductionmentioning
confidence: 99%